1979
DOI: 10.6028/jres.084.018
|View full text |Cite
|
Sign up to set email alerts
|

Theory of flow-induced fibril formation in polymer solutions

Abstract: A treatment of the formation of a basic core fibril (shish) of the type that is ge nerated by fl ow-indu ced crystallization of a polymer from solution is given that features the concept of cu mulative strain. Multiple nucleation acts by flow-elongated molecules produce an e mbryonic fibril that is a connec ted set of bundlelike nucle i. Surface s tress resulting from repu ls ion of the quasi-random coil c hains in the amorphous zone between the nucle i or c rystallit es builds up at the bundl e e nds as the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
(65 reference statements)
0
15
1
Order By: Relevance
“…Davis et al [18] showed that the cross-sectional area occupied by each chain is inversely proportional to the fold period of the axial surface of the crystal. Hoffman demonstrated that then the cross-sectional area of the strained chain is inversely proportional to the thickness of the core-fibril [10]. This means that the thinner fibril should exhibit a larger lattice expansion.…”
Section: Crystallization Models For the Formation Of Core-fibrilsmentioning
confidence: 99%
See 3 more Smart Citations
“…Davis et al [18] showed that the cross-sectional area occupied by each chain is inversely proportional to the fold period of the axial surface of the crystal. Hoffman demonstrated that then the cross-sectional area of the strained chain is inversely proportional to the thickness of the core-fibril [10]. This means that the thinner fibril should exhibit a larger lattice expansion.…”
Section: Crystallization Models For the Formation Of Core-fibrilsmentioning
confidence: 99%
“…This can lead to relatively uniform expansion effects in the crystals [10,16]. In particular, an expansion effect can be expected arising from the ciliary bridges.…”
Section: Crystallization Models For the Formation Of Core-fibrilsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of the formation of fibrils in polymer solutions, Hoffman 54 proposed a similar mechanism to explain the formation of stable crystallites when a shear stress is applied to the fluid. The origin of such a stress accumulation around the crystallite was in this case a consequence of the cumulative strain resulting in an expansion of the chains at the surface of the crystallites.…”
Section: Introductionmentioning
confidence: 99%